The SAGE handbook of online research methods - Fielding, Nigel; Lee, Raymond M., 1946-; Blank, Grant; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2008)
This handbook provides comprehensive coverage of contemporary and developing Internet and online social research methods, spanning both quantitative and qualitative research applications.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Internet research; Social sciences -- Research; Electronic books